Effect of inbreeding on productive parameters in Costa Rican Holstein and Jersey cows - Aguirre Valverde, Judyana (2013)
A retrospective longitudinal study was conducted with 208 148 records of Holstein and Jersey cows from 545 specialized dairy herds present in the VAMPP Bovino National Data Base, of the Regional Center of Informatics for Sustainable Animal Production (CRIPAS), School of Veterinary Medicine, National University, from 1995 to 2010. The effect of inbreeding on the 305-day-corrected milk yield (PC305d) and productive life--calculated according to the USDA formula--, was analyzed by multiple linear regression, using a mixed model. A cut-off point value of ≥6.25% for the coefficient of inbreeding (F) was used to delimit high F levels. In addition, the possibility for a cow with F≥6.25% having low productive parameters was calculated by non conditional logistic regression. The survival analysis, using the Weibull distribution, was used to determine the effect of inbreeding on the productive life. A 17.9% of animals with inbreeding was found, being Holstein the race with more inbred cows, although Jersey had, on the average, the highest inbreeding levels. Cows with low F produced +140.4 kg PC305d compared to those having elevated F levels (p<0.01). Cows with high F had increased risk of PC305d <5000 kg (Jersey) and <6500 kg (Holstein) than those with low inbreeding coefficient (OR=1.3; IC95%: 1.2-1.4). It was observed, +10.3 months and +19.3 months of productive life (USDA) for Holstein and Jersey cows with low inbreeding coefficient. We conclude that there is a negative effect of elevated inbreeding coefficient on the productive life (USDA) and the PC305d of Holstein and Jersey cows in Costa Rican dairy farms.